Activating Learners in Foreign Language Lessons - Gondova, Danica (Communications - Scientific letters of the University of Zilina, 2007)
The article deals with the importance of activating methods that can be applied in the process of foreign language teaching and learning and are used to stimulate learners’ interest in languages and to motivate them. If learners do things actively in lessons, if they discover language rules and vocabulary for themselves, they feel engaged and involved in the process and they can remember new structures and lexical units better and for a longer period of time. In the process of active learning teacher becomes a facilitator whose most important task is to facilitate learning by following cognitive, affective and linguistic principles, by creating a supportive atmosphere in the classroom and by exposing learners to as much language as possible not only at school but also at home.